Stuck in the middle? Structural change and productivity growth in Botswana - McCaig, Brian; McMillan, Margaret S.; Verduzco-Gallo, Íñigo; Jefferis, Keith (International Food Policy Research Institute, 2017)
In 1966 when Botswana gained independence, it was one of the poorest countries in the world. But by 1986, Botswana had achieved middle-income status, and in 2005, the World Bank classified it as an upper-middle-income country. The only other country to enjoy such rapid economic growth over such a long period is China—an average of 9 percent between 1968 and 2010. Botswana has also maintained democracy throughout its recent history, and this combination of economic and political success has earned it the reputation of an “African success story” (Acemoglu, Johnson, and Robinson 2002). Botswana’s rapid economic growth has nonetheless left many individuals behind. Unemployment is a major issue, particularly among the young. Income inequality is extremely high, as is poverty. As such, it is important to understand the sources of Botswana’s economic growth to better appreciate where it may come from in the future and what prospects it has for being more inclusive.